Upadacitinib Achieves Clinical and Endoscopic Outcomes in Crohn's Disease Regardless of Prior Biologic Exposure - Peyrin-Biroulet, Laurent; Panaccione, Remo; Louis, Edouard; Atreya, Raja; Rubin, David T.; Lindsay, James O.; Siffledeen, Jesse; Lukin, Dana J.; Wright, John; Watanabe, Kenji; Ford, Sharanya; Remple, Valencia P.; et al. (Clinical Gastroenterology and Hepatology, 2024)
Background & Aims: Upadacitinib, an oral Janus kinase inhibitor, achieved significantly higher rates of clinical remission and endoscopic response vs placebo during induction (U-EXCEL [NCT03345849], U-EXCEED [NCT03345836]) and maintenance (U-ENDURE [NCT03345823]) treatment in patients with moderate-to-severe Crohn's disease. Prior biologic failure is often associated with reduced responses to subsequent therapies. This post hoc analysis assessed upadacitinib efficacy by prior biologic failure status. Methods: Patients were randomized to placebo or upadacitinib 45 mg (UPA45) for 12 weeks (induction). UPA45 clinical responders were enrolled in U-ENDURE and rerandomized to placebo, upadacitinib 15 mg, or upadacitinib 30 mg (UPA30) for 52 weeks. Assessments were by prior biologic failure. Results: Of 1021 patients, 733 (71.8%) had prior biologic failure. Across outcomes and subgroups, upadacitinib-treated patients achieved higher rates vs placebo. During induction, upadacitinib had higher rates vs placebo for clinical remission based on stool frequency/abdominal pain score (without failure: 54.0% vs 28.3%; with failure: 42.2% vs 14.1%) and endoscopic response (without failure: 52.0% vs 16.2%; with failure: 35.7% vs 5.3%). In maintenance, the greatest treatment effect (upadacitinib vs placebo) was among patients with prior biologic failure treated with UPA30 (clinical remission without failure: 58.5% vs 32.7%; with failure: 42.5% vs 8.7%; endoscopic response without failure: 43.9% vs 17.9%; with failure: 38.9% vs 4.0%). Patients without vs with prior biologic failure had fewer adverse events. Conclusions: Upadacitinib led to higher absolutes rates of clinical and endoscopic outcomes in patients without vs with prior biologic failure. Patients treated with upadacitinib achieved greater rates of clinical and endoscopic improvements vs placebo, regardless of prior biologic exposure. ClinicalTrials.gov: NCT03345849, NCT03345836, NCT03345823.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Biologic Failure; Biologic Naive; Crohn's Disease; JAK Inhibitor; Upadacitinib